2012
DOI: 10.1155/2012/524019
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antinociceptive, and Anti-Inflammatory Effects of Carotenoids Extracted from Dried Pepper (Capsicum annuumL.)

Abstract: Carotenoids extracted from dried peppers were evaluated for their antioxidant, analgesic, and anti-inflammatory activities. Peppers had a substantial carotenoid content: guajillo 3406 ± 4 μg/g, pasilla 2933 ± 1 μg/g, and ancho 1437 ± 6 μg/g of sample in dry weight basis. A complex mixture of carotenoids was discovered in each pepper extract. The TLC analysis revealed the presence of chlorophylls in the pigment extract from pasilla and ancho peppers. Guajillo pepper carotenoid extracts exhibited good antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 69 publications
(82 reference statements)
2
58
0
9
Order By: Relevance
“…Carotenoids possess a range of important biological activities. They are potent antioxidants acting as scavengers of singlet molecular oxygen, peroxyl radicals and reactive nitrogen species [15]. The consumption of carotenoid-rich foods reduces the incidence of several disorders such as cancers, cardiovascular diseases, age-related macular degeneration, cataracts, diseases related to compromised immune function, and other degenerative diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoids possess a range of important biological activities. They are potent antioxidants acting as scavengers of singlet molecular oxygen, peroxyl radicals and reactive nitrogen species [15]. The consumption of carotenoid-rich foods reduces the incidence of several disorders such as cancers, cardiovascular diseases, age-related macular degeneration, cataracts, diseases related to compromised immune function, and other degenerative diseases [16].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown the induction of nonenzymatic and enzymatic antioxidants in legumes subjected to water deiciency. Antioxidant enzymes are proteins that catalyse the detoxiication of free radicals by using protons or electrons released by nonenzymatic antioxidants [68]. In the case of water deicit and salinity, several workers have reported the increase of these activities in the nodules under stress [41].…”
Section: Antioxidant Defencementioning
confidence: 99%
“…The total carotenoid content were estimated according to method described by Hernández-Ortega et al [23]. Pigment concentration was determined spectrophotometrically at 472 and 508 nm wavelengths in a UV-Vis spectrophotometer (Genesys 10 UV, Thermo Scientific, Wisconsin, USA).…”
Section: Total Carotenoids and Total Phenolic Compoundsmentioning
confidence: 99%
“…The results are expressed as mg gallic acid equivalent per gram of dry sample [24]. [23]. Phenolic compounds were identified using the method described by Hayat et al [25].…”
Section: Total Carotenoids and Total Phenolic Compoundsmentioning
confidence: 99%